Comparison Of Moving Average Methods For Forecasting Recommendation Letters By Licensing Type In Pamekasan Regency - Ani Alfiya Fahad; Kuzairi; Tony Yulianto (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
Recommendation letters play an important role in various aspects of life, such as applying for assistance, business permits, and support for social activities. This letter serves as a means of providing official support from the authorities to individuals or groups in need, whose numbers need to be predicted for sustainable management. The forecasting method that is widely used is Moving Average, and in this study, In this study, predictions of the number of issued recommendation letters from 2021 to 2024 were carried out using the single moving average, exponential moving average and weighted moving average methods. The results of the study showed that the single moving average method was proven to be the best method with a MAPE value of (43.8073), followed by the exponential moving average method with a MAPE value of (47.0741), and the weighted moving average with a MAPE value of (47.0741). So the forecasting method that is considered feasible is the single moving average method as shown by its MAPE range value. Thus, the single moving average method is determined to be the best forecasting method for predicting future recommendation letter issuance.